Collaboration between a cis-interacting natural killer cell receptor and membrane sphingolipid is critical for the phagocyte function - Karyu, Hitomi; Niki, Takahiro; Sorimachi, Yuriko; Hata, Shoji; Shimabukuro-Demoto, Shiho; Hirabayashi, Tetsuya; Mukai, Kojiro; Kasahara, Kohji; Takubo, Keiyo; Goda, Nobuhito; Honke, Koichi; Taguchi, Tomohiko; et al. (Frontiers in Immunology, 2024)
Inhibitory natural killer (NK) cell receptors recognize MHC class I (MHC-I) in trans on target cells and suppress cytotoxicity. Some NK cell receptors recognize MHC-I in cis, but the role of this interaction is uncertain. Ly49Q, an atypical Ly49 receptor expressed in non-NK cells, binds MHC-I in cis and mediates chemotaxis of neutrophils and type I interferon production by plasmacytoid dendritic cells. We identified a lipid-binding motif in the juxtamembrane region of Ly49Q and found that Ly49Q organized functional membrane domains comprising sphingolipids via sulfatide binding. Ly49Q recruited actin-remodeling molecules to an immunoreceptor tyrosine-based inhibitory motif, which enabled the sphingolipid-enriched membrane domain to mediate complicated actin remodeling at the lamellipodia and phagosome membranes during phagocytosis. Thus, Ly49Q facilitates integrative regulation of proteins and lipid species to construct a cell type-specific membrane platform. Other Ly49 members possess lipid binding motifs; therefore, membrane platform organization may be a primary role of some NK cell receptors.